Technology and Need as Starting Points for Innovation - Experiences from Multidisciplinary Student Teams - T.Utriainen; V.Taajamaa; R.Movva; J.Kurikka (My University, 2022)
In research organizations the starting point for innovation is typically technology developed in-house and the application of it in a novel field. Working at an international research institution, the authors have experimented a new approach by creating course structures that are designed to start with a need instead of technology. Such structures include Innovation for Change (IfC) and Challenge Based Innovation (CBI) amongst others.
2017 ASEE Annual Conference & Exposition